S586 Indian Journal of Pharmaceutical Education and Research |Vol 54 | Issue 3 [Suppl] | Jul-Sep, 2020 Original Article www.ijper.org HPTLC Densitometric Quantification of Kaempferol from Leaves of Euphorbia neriifolia - Mali, Prashant Y.; Goyal, Swapnil (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: To study HPTLC densitometric quantification of kaempferol in aqueous extract fraction (EN6) of leaves of Euphorbia neriifolia Linn. Methods: Chromatographic method was employed on pre-washed and pre-activated 10.0 x 10.0 cm aluminum Lichrosphere HPTLC plates pre-coated by silica gel 60 F254 of 0.2 mm thickness layer as a stationary phase. Solvent system toluene: ethyl acetate: formic acid (6:4:1 v/v/v) was used. Densitometric analysis of kaempferol was carried out at 254 nm in absorptionreflectance mode. Percent content of kaempferol was quantified using proposed HPTLC densitometric method. The method was validated by ICH guidelines for its linear range, linearity, LOD and LOQ, specificity, precision, reproducibility and recovery studies. Results: HPTLC finger printing analysis showed that Rf value of peak of kaempferol (Rf 0.91) was closely compacted with aqueous extract fraction (EN6; Rf 0.90) that indicates identification of kaempferol. Percent content of kaempferol was quantified and found to be 0.024817% in aqueous extract fraction (EN6) for 10 μl volume applied. Linear range was found100-600 ng/spot with correlation coefficient 0.99834. LOD and LOQ were found 100 and 300 ng. Proposed method was specific. The % CV for intra-day was 2.422 and inter-day was 2.522 at concentration of 400 ng/spot. The % CV was found 2.1, hence the method was reproducible. Average percent recovery was 95.57% in aqueous extract fraction (EN6), therefore, the method was found to be accurate. Conclusion: Developed HPTLC method was found to be simple, specific, precise, reproducible and accurate. Here, the first time we have reported HPTLC method for kaempferol in aqueous extract fraction (EN6). However, there is a requirement to carry forward these studies by using some other standard markers in aqueous extract fraction (EN6) of E. neriifolia leaves for exploring its phyto-constituents that could have therapeutic potential in various diseases.
Keywords: Euphorbia neriifolia Linn; Aqueous extract fraction; Leaves; HPTLC; Kaempferol; Identification; Quantification; Validation